P-124 Evolution and revolution in managing hospice patients' blood glucose levels. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Bell, Sarah
Abstract : Background: On outpatient review, a recent in-patient initiated on steroids was newly diabetic. Given the minimal hospice guidance on blood glucose management, a quality improvement programme was initiated. Aim: Evolution and revolution in care to provide high standards of blood glucose management in patients taking steroids, with diabetes or nearing end of life. Method: Process over four years, informed by three audit cycles. Firstly, development of hospice standards for blood glucose management in patients with diabetes or on steroids, based on Diabetes UK End of Life Diabetes Care Recommendations (3rd ed., 2018), which was adopted as hospice policy. Overall, standards were to ensure: Recording of blood glucose levels and documentation of clear, appropriate management plans for diabetic patients or on steroids; Reviewing of blood glucose management in last days of life; Accurate recording and prescribing of blood glucose lowering drugs. Secondly, recurring multifaceted and multidisciplinary education of staff on diabetes and the importance of blood sugar management, supported by publicity about the new policy and hospice standards in all clinical areas. Thirdly, change of existing blood glucose monitoring proforma to include more detail and increased guidance regarding target blood glucose levels. Results: Initial audit demonstrated inadequate management plans, no blood glucose target range setting, poor blood glucose monitoring, no last days of life review of management or monitoring of blood glucose levels for patients on steroids. Second audit demonstrated significant improvement in management of patients with diabetes, including at end of life but continued poor monitoring and management of blood glucose in patients with steroids. Final audit demonstrated high compliance in all areas. Conclusion: Evolution of clinical management culture may be challenging and prolonged. Combination of techniques is necessary, including repeated, multidisciplinary education of the underlying issues, publicity regarding change, practical guidance for staff and revolution in aspects of multidisciplinary working and care.